We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
136
2
avatar+404 

If t(x) = 3-g(x) and g(x) = √ x, then what is t(g(16))?

 May 7, 2019
 #1
avatar+196 
0

The nested functions at the end mean that you put 16 into the function g, then take what you get and put it in the t function (sometimes written as (t o g)(x) )

You can rewrite function t as t(x)=3-√x, because the g function inside of it means that you subrtact the g of x from 3

 May 7, 2019
 #2
avatar+104882 
+1

f(g(16))........means that we put 16 into g, first.....and evaluate....

 

Then...we put that result into f

 

So

g(16)  =  sqrt (16)  = 4

 

And

 

f(4)  = 3 - g(16)  =   3 - sqrt (16)  =  3 - 4  =   -1

 

 

cool cool cool

 May 7, 2019

7 Online Users

avatar